2021
DOI: 10.1002/pits.22560
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with the day‐to‐day: Harnessing school climate to address the effects of student victimization on academic performance

Abstract: Research suggests that parents and principals perceive school shootings as one of the leading threats to school safety and among the most likely hazardous events that would affect safety at school. However, exposure to nonfatal victimization, such as fighting, threats, theft, vandalism, bullying, hate crimes, and gang activity, has become far more common in today's schools. Using data from students in eight schools across one urban school district in the northeast United States, this study examines within‐scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As noted by Chaux (2012), victim students experience negative emotions, such as stress and anxiety at school, which might contribute to maladjustment to the school environment (Nansel et al, 2003). The fear of exposure to peer bullying also negatively affects school attendance (Cuellar et al, 2021; Jan & Husain, 2015; Smith et al, 2004) due to feelings of unsafety (Esbensen & Carson, 2009; Nazir & Bala, 2018; Rigby, 2007). Schwartz et al (2005) found that victim students may develop negative attitudes toward school, leading to absenteeism, missed lessons and homework, and reduced engagement in social activities after school.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted by Chaux (2012), victim students experience negative emotions, such as stress and anxiety at school, which might contribute to maladjustment to the school environment (Nansel et al, 2003). The fear of exposure to peer bullying also negatively affects school attendance (Cuellar et al, 2021; Jan & Husain, 2015; Smith et al, 2004) due to feelings of unsafety (Esbensen & Carson, 2009; Nazir & Bala, 2018; Rigby, 2007). Schwartz et al (2005) found that victim students may develop negative attitudes toward school, leading to absenteeism, missed lessons and homework, and reduced engagement in social activities after school.…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to compare victim students with non‐bullied peers in terms of their achievement in TIMSS and PIRLS exams and to identify potential moderators of the relationship between peer bullying and academic achievement. Previous research on the effect of peer bullying on academic achievement has been primarily limited to data obtained from nonstandardized achievement tests or the standardized achievement of specific countries (see Carrasco et al, 2022; Cuellar et al, 2021; Engel et al, 2009; Huang, 2022; Yu & Zhao, 2021) or individual studies or nonstandard test scores (Fry et al, 2018; Glew et al, 2005; Strøm et al, 2013). This prevalent problem has rarely been discussed in South‐Eastern Europe and East Asian countries (Benbenishty & Astor, 2019).…”
Section: Peer Bullying and Academic Achievementmentioning
confidence: 99%
See 1 more Smart Citation
“…Students who perpetrate violence in school are at increased likelihood to drop out of high school, particularly among disadvantaged male youths (Staff & Kreager, 2008). In general, adolescent exposure to violence and peer delinquency is associated with greater health risk behaviors, poor mental health outcomes and lower high school performance and retention rates (Boynton-Jarrett et al, 2012; Cuellar, Coyle & Weinreb, 2021). Moreover, exposure to violence and maladaptive student behavior in school has been linked to aggression, particularly among secondary school youth (O’Keefe, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%